Falcon's feathers by Ron Roy; illustrated by John Steven Gurney - Roy, Ron; Gurney, John, ill (New York Random House, 1998)
Josh and his two friends look for the person who stole a peregrine falcon from its nest.
A Stepping Stone book.
Keywords: Peregrine falcon-Fiction; Falcons-Fiction; Mystery and detective stories